Interactive effect of motivation, job satisfaction, and job performance - Wildan, Wildan; Aryanda, Aryanda; Saputra, Datep Purwa (2017)
The research aims to confirm and test the interactive effect of motivation, job satisfaction and job performance.This study was applied to employees of Sharia Financial Institutions in Jakarta.The number of respondents is 70 employees with randomly selected samples stratified.Research analysis data using multiple indicators within analysed using structural equation model.The results showed that there was a positive interactive effect motivation on job performance and job performance on motivation, job satisfaction on job performance and job performance on job satisfaction, motivation on job satisfaction and job satisfaction on motivation.